Parallel paired electrolysis of green oxidizing agents by the combination of a gas diffusion cathode and boron-doped diamond anode - Hamm, Christin M.; Schneider, Selina; Hild, Stefanie; Neuber, Rieke; Matthée, Thorsten; Krümberg, Jens; Stöckl, Markus; Mangold, Klaus-Michael; Kintrup, Jürgen (Frontiers in Catalysis, 2024)
The generation of “green” oxidizing agents by electrochemical synthesis opens the field for sustainable, on-demand, and on-site production, which is often based on non-critical starting materials. In this study, electrosyntheses were carried out on different cathode and anode materials. In half-cell experiments, the cathodic synthesis of peracetic acid (PAA) was investigated on gas diffusion electrodes (GDEs), reaching 22.6 mmol L−1 of PAA with a current efficiency (CE) of 7.4%. Moreover, peroxodicarbonate (PODIC®) was produced anodically on boron-doped diamond (BDD) electrodes with concentrations as high as 42.7 mmol L−1 PODIC® and a CE of 30.3%. Both cathodic and anodic processes were individually examined and improved. Finally, the half-cell reactions were combined as a proof of concept in a parallel paired electrolysis cell for the first time to achieve an increased overall CE.